Perencanaan Kawasan Pantai Wong Polo Desa Kota Pari di Kecamatan Pantai Cermin - Kiki Hariwahyuna; Rahmadhani Fitri; Novalinda; Faurantia Forlana Sigit (Universitas Medan Area, 2023)
The potential of natural resources owned by the Wong Polo beach tourism area in the Pantai Cermin sub-district needs to be explored and developed into a tourism sector without good planning, which will result in loss and quality degradation of the area that is not expected. Based on the results of the study, it is shown that the identification of the physical aspects of the beach condition supports the development of beach tourism, which is one of the beach tourism destinations located in Hamlet XI, Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency, North Sumatra. This Wong Polo beach area has white sand beaches and Mangrove forest areas based on nature tourism and the pattern of structuring the zones in the Wong Polo beach area leads and is oriented towards the waters as well as to facilitate these tourist attractions into areas of a beach of interest visitors.